Program Literasi Informasi di Sekolah Polisi Negara Hinai Polisi Daerah Sumatera Utara - Dian Ramadani; Abdul Karim Batubara; Muslih Fathurrahman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to (1) evaluate the efforts made by the North Sumatra Regional Police Hinai State Police School Library in the information literacy program, (2) assess the results achieved by students from the information literacy program, and (3) identify inhibiting factors in the implementation of the information literacy program in the library of the North Sumatra Police Hinai State Police School. The research method used was qualitative with a descriptive approach, using interview techniques, and research subjects were selected through purposive sampling. The results of the research show that the information literacy program in the North Sumatra Regional Police Hinai State Police School library has produced various activity programs, such as a 15 minute reading program every two weeks and reading awards. SPN Hinai North Sumatra Regional Police students are able to understand and utilize information from the library for DIKTUBA (Non-Commissioned Officer Education) POLRI assignments. Obstacles in implementing the program include a lack of media and human resources skilled in information literacy as well as a lack of adequate facilities and infrastructure.